2003
DOI: 10.1037/0003-066x.58.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity/spirituality and health: A critical review of the evidence for biological pathways.

Abstract: The authors review evidence regarding the biological processes that may link religiosity/spirituality to health. A growing body of observational evidence supports the hypothesis that links religiosity/spirituality to physiological processes. Although much of the earliest evidence came from cross-sectional studies with questionable generalizability and potential confounding, more recent research, with more representative samples and multivariate analysis, provides stronger evidence linking Judeo-Christian relig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
252
0
18

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(280 citation statements)
references
References 54 publications
10
252
0
18
Order By: Relevance
“…A variety of studies find R/S is related to lower or reduced blood pressure (Friedlander, Kark, Kaufmann, & Stein, 1985;Graham, Taylor, Hovell, & Siegel, 1983;Levin & Vanderpool, 1989; Teresa E. Seeman, Dubin, & Seeman, 2003;Sloan & Bagiella, 2002). In perhaps the first study on church attendance and blood pressure published in the first issue and year of the Journal of Behavioral Medicine in 1978, Graham and colleagues found lower systolic and diastolic blood pressure in frequent church attenders compared to infrequent church attenders (Graham et al, 1978).…”
Section: Spirituality and Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…A variety of studies find R/S is related to lower or reduced blood pressure (Friedlander, Kark, Kaufmann, & Stein, 1985;Graham, Taylor, Hovell, & Siegel, 1983;Levin & Vanderpool, 1989; Teresa E. Seeman, Dubin, & Seeman, 2003;Sloan & Bagiella, 2002). In perhaps the first study on church attendance and blood pressure published in the first issue and year of the Journal of Behavioral Medicine in 1978, Graham and colleagues found lower systolic and diastolic blood pressure in frequent church attenders compared to infrequent church attenders (Graham et al, 1978).…”
Section: Spirituality and Blood Pressurementioning
confidence: 99%
“…Other possible mechanisms include improved health behaviors, access to social resources, improved coping resources, prayer (Ironson et al, 2002;Pargament, 1997), promotion of positive emotions (e.g., forgiveness) (McCullough & Worthington, 1999), taking part in religious rites (Benson, 1983;Bernardi et al, 2001), personal faith (Ellison & Levin, 1998;McCullough et al, 2000;Strawbridge et al, 2001), positive reappraisal (Carrico et al, 2006), and benefit finding (Dedert et al, 2004). R/S could work through physiological mechanisms such as neurohormonal function and cardiovascular function (Teresa E. Seeman et al, 2003). R/S could buffer cardiovascular reactivity through one, some, or all of these behavioral, cognitive, and physiological mechanisms.…”
Section: Spirituality As Buffer To Stressmentioning
confidence: 99%
“…Additionally, there are factors that negatively affect the patient's psychological state as well [24]. These include perceived threat to one's life, the uncontrollable and unpredictable nature of one's condition, and the state of apprehension and hopelessness , which can have a considerable effect on the patient's thoughts , emotions, and behaviors [25][26][27]. Indeed, the lingering, long-term psychological effects such as anxiety , depression, and post-traumatic stress disorder commonly occur in response to critical illnesses [28,29].…”
Section: Hospitalizationmentioning
confidence: 99%
“…Regarding religion and health, Seeman, Dubin and Seeman's (2003) review of studoes related to biological processes indicates that "spirituality is linked to healthrelated physiological processes -including cardiovascular, neuroendocrine, and immune function" (p. 53). They found that religious influence on health is particularly pronounced in studies of meditation, although they acknowledge that more evidence needed.…”
Section: Religion and Individual Well-beingmentioning
confidence: 99%